Analysis of Factors Affecting Social Media Utilization of Extension Agents - Shanmuka, A.; Lenin, V.; Sangeetha, V.; Muralikrishnan, L.; Ramasubramanian, V.; Arora, Alka (Indian Journal of Extension Education, 2022)
Digitalization of communication networks through social media platforms is the most important tool to increase the reach and impact of agricultural advisory services. A profound need to study the extent of usage of social media by extension agents and factors influencing its usage was felt and to analyze the extent of usage, a composite index was developed during 2021 by using seven sub-indices that had a Cronbach alpha value of 0.903. To study the extent of usage 160 extension agents through a proportionate random sampling method were selected from Andhra Pradesh where the majority of the extension agents had a medium extent of usage which accounts for 44.37 per cent. Based on the correlational analysis it is found that innovative proneness (p
Keywords: Social media; Extent of usage index; Socio personal; Job-related characteristics